Effectiveness Of Young Areca Nut Simplisia On Healing Perineal Wounds In Post-Participant Mothers At The Midwife Wanti Clinic In Medan - Sikumbang, Sri Rintani; Harahap, Hasanah Pratiwi; Padilah, Afrahul; Rusmiyati, Rusmiyati; Delena, Qori Q (Jurnal Maternitas Kebidanan, 2025)
One of the organs that often experiences injury or wounds during childbirth is the perineum, which occurs due to forced pushing during childbirth. Nearly 90% of the childbirth process, mothers experience perineal tears, either intentionally or through an episiotomy. Complications that often occur from birth canal tears are characterized by long wound healing times and even infection. Preventive efforts to prevent infection can be done by providing morphological and non-morphological therapy. The purpose of this study was to determine the effectiveness of young Areca Nut fruit simplicia with perineal wound healing at the Wanti Medan Clinic in 2025. The design of this study used the True Experimental method, with a Posttest Only Control Group Design approach. The sampling technique used Population Sampling with a total of 20 postpartum mothers starting from day 1 postpartum with 10 people as the intervention group and 10 people as the control group. Univariate and bivariate data analysis. The results of the study showed statistical results using the Mann-Whitney test, with a p-value of 0.000 < α 0.05, indicating a significant effectiveness of using young areca nut extract on perineal wound healing. Healing occurred more quickly in the intervention group, with an average healing time of <6 days for 9 people (90.0%), classified as fast. Meanwhile, in the control group, an average healing time of 6-7 days for 6 people (60.0%), classified as normal. The conclusion of this study is the effectiveness of young areca nut extract on perineal wound healing in postpartum women at the Wanti Clinic in Medan in 2025. It is recommended that healthcare workers, especially at the Wanti Clinic in Medan, apply complementary therapy using young areca nut extract in perineal wound care.